The effectiveness of a video based preference assessment in identifying social reinforcers. Issue 1 (2nd January 2018) - Huntington, Rachelle N.; Higbee, Thomas S.
ABSTRACT: Stimulus preference assessments have been established as an effective way to identify potential reinforcers. Less is known, however, about the effectiveness of these assessments at predicting potential social reinforcers. This study examined the utility of a video-based preference assessment for accurately identifying reinforcing social activities. Using a forced-choice format, videos were presented side-by-side that portrayed various social interactions. This assessment generated a hierarchy of most and least preferred social stimuli for each participant. The reinforcing effectiveness of the highest- and lowest-preferred stimuli was then evaluated in a reinforcer assessment. For each of the three participants, the stimuli selected most often, or the highest preferred, increased responding above baseline and low-preference conditions. These results indicate that video representations of social stimuli may accurately identify preference hierarchies. Implications for the use of video technology in assessing social preferences are discussed.